Mediasi sebagai Alternatif Penyelesaian Sengketa Pembayaran Letters of Credit - Erico Dian Pratama; Christin Marito Lumban Toruan; Zhafira Naifah Anidania; Rizha Claudilla Putri (Pusat Riset dan Inovasi Nasional, 2026)
Letter of Credit or L/C is a payment instrument in international trade transactions. Payment through a Letter of Credit is the most ideal form of payment in providing payment certainty, because in its mechanism, L/C requires payment to the seller through a bank guarantee with the fulfillment of the conditions specified in the document. Fraudulent letters of credit are disputes between parties in the execution of L/C payments caused by errors or irregularities due to fraud. As a result, in international civil agreements, such agreements are deemed invalid. Mediation is a method of dispute resolution through non-litigation channels. In mediation, the dispute resolution mechanism is carried out by using a third party called a mediator. This method is highly dependent on the trust of the disputing parties in the mediator. In carrying out their duties, mediators act based on the principles of neutrality, confidentiality, voluntariness, empowerment, and as a provider of recommendations in the course of mediation for dispute resolution. Generally, mediation as a method is rarely applied in cases of international civil dispute resolution, because the resolution of international civil payment disputes is carried out through arbitration. Arbitration is a method of dispute resolution based on an arbitration agreement. An arbitration agreement is an agreement agreed upon by both parties to submit and surrender all matters to an arbitrator.